Characterization of Bimetallic Fe-Ru Oxide Nanoparticles Prepared by Liquid-Phase Plasma Method - Lee, Sung-Jin (Nanoscale Res Lett, 2016)
The bimetallic Fe-Ru oxide nanoparticles were synthesized in the liquid-phase plasma (LPP) method which employed iron chloride and ruthenium chloride as precursors. The active species (OH·, H(α), H(β), and O(I)) and the iron and ruthenium ions were observed in the plasma field created by the LPP process. The spherical-shaped bimetallic Fe-Ru oxide nanoparticles were synthesized by the LPP reaction, and the size of the particles was growing along with the progression of the LPP reaction. The synthesized bimetallic Fe-Ru oxide nanoparticles were comprised of Fe(2)O(3), Fe(3)O(4), RuO, and RuO(2). Ruthenium had a higher reduction potential than iron and resulted in higher ruthenium composition in the synthesized bimetallic nanoparticles. The control of the molar ratio of the precursors in the reactant solution was found to be employed as a means to control the composition of the elements in bimetallic nanoparticles.